The Referee Is Not an Employee but Must Endure Full Subordination: The Precarious Work of Soccer Referees in Brazilian Football - Farias Alves Correia, Gabriel; Palhares dos Santos, José Vitor; Fróes Couto, Felipe; Carrieri, Alexandre de Pádua (Organizações & Sociedade, 2025)
Although referees play a crucial role in soccer, they are neither recognized nor valued as a professional category. This article aims to explore the precarious working conditions faced by Brazilian soccer referees through the accounts of former referees from Minas Gerais, Brazil, who were affiliated with the Minas Gerais Soccer Federation (FMF). To achieve this, we drew on theoretical discussions of job insecurity, defined by Druck (2011) as a condition experienced by workers, encompassing technological changes, restructuring, legislation, and instability in labor relations. Methodologically, we employed a combination of historical and qualitative approaches to conduct a memory-based investigation. A total of 21 semi-structured narrative interviews were conducted and triangulated with historical documents accessed during fieldwork, alongside notes recorded in a research-specific notebook. The findings, analyzed through thematic narrative analysis, reveal seven key categories of precariousness: lack of preparation, class fragmentation, hegemony of governing entities, lack of infrastructure, double shifts, retaliation, and vulnerability to violence. This article contributes to discussions on the inconsistencies inherent in nonemployment labor arrangements, using the experiences of former referees from Minas Gerais in Brazilian soccer as a lens to examine broader patterns of work and social dynamics. Ultimately, it aims to shed light on the often invisible labor of individuals with limited power in social hierarchies.